2007
DOI: 10.4081/ijas.2007.1s.734
|View full text |Cite
|
Sign up to set email alerts
|

Foot dermatitis and productive traits in broiler chickens kept with different stocking densities, litter types and light regimen

Abstract: The purpose of the research was to study the effects of high and low stocking density of broiler chickens, different types of litter and the adoption of short and long lighting regimen on broiler welfare through the evaluation of their productivity and incidence of foot pad dermatitis. 2,400 male Ross 508 were divided into 8 groups of four replicates each and reared in 32 pens according to a 3 factors experimental design of two levels each: low (LD) or high (HD) stocking density (11 and 14 birds/m2 for LD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 6 publications
2
27
0
2
Order By: Relevance
“…Sorensen et al (1999) reported less severe foot pad dermatitis lesions on extended light duration. However, Sirri et al (2007) compared broilers on 16L:8D with those on 23L:1D photoperiod and found no differences for this condition. Similarly, it was reported that the near-continuous photoperiod resulted in descreased severity of foot pad dermatitis, while there was no statistical significance among photoperiod groups.…”
Section: Discussionmentioning
confidence: 93%
“…Sorensen et al (1999) reported less severe foot pad dermatitis lesions on extended light duration. However, Sirri et al (2007) compared broilers on 16L:8D with those on 23L:1D photoperiod and found no differences for this condition. Similarly, it was reported that the near-continuous photoperiod resulted in descreased severity of foot pad dermatitis, while there was no statistical significance among photoperiod groups.…”
Section: Discussionmentioning
confidence: 93%
“…One of the solutions to reduce the percentage of contact dermatitis might be to reduce the humidity inside the house or add to the litter during the rearing period in order to limit the degradation of the litter. As suggested in a previous study (Sirri et al, 2007), the change of litter type could be another solution, because flocks reared on wood shavings exhibited less dermatitis than those reared on straw.…”
mentioning
confidence: 90%
“…A wide range of materials could be used as broiler litter: rice hulls, ground corncobs, stump chips, pine sawdust, white wood shavings, bark and chips, pine bark, clay sand, coconut husk, Guinea grass, newspaper, corn cob, wheat straw, ground rapeseed straw and silage maize (Grimes et al, 2002;Sirri et al, 2007;Meluzzi et al, 2008;Garcês et al, 2013). Each of these materials has advantages and disadvantages, but different particle size of these materials was seen to be one of the most important factors and has been examined as a contributing factor in the development of footpad dermatitis (FPD) (Shepherd et al, 2010).…”
Section: Introductionmentioning
confidence: 99%